NIHR Global Health Research Group on Vaccines for vulnerable people in Africa (VAnguard): Concept and Launch event report - Zirimenya, Ludoviko; Zalwango, Flavia; Karanja , Henry K.; Natukunda, Agnes; Kiwanuka, Achilles; Chibita, Monica (NIHR Open Research, 2023)
Vaccination is an important public health intervention, but not everyone benefits equally. Biological, social and structural factors render some communities vulnerable and unable to secure optimal health benefits from vaccination programmes. This drives health inequity and undermines wider vaccine impact by allowing the persistence of non-immune communities as foci for recurrent disease outbreaks. The NIHR Global Health Research Group on Vaccines for vulnerable people in Africa (VAnguard) aims to understand how biological, social, and structural factors interact to impair vaccine impact in vulnerable African communities.